Empirical analysis on exchange rate fluctuation and sectoral stock returns in Malaysia - Rambeli @ Ramli Norimah, Hashim Emilda, Hashim Asmawi, Awang Marikan Dayang Affizzah, Podivinsky Jan M., (N/A, 2017)
Empirical analysis on exchange rate fluctuation and sectoral stock returns in Malaysia by Rambeli @ Ramli Norimah, Hashim Emilda, Hashim Asmawi, Awang Marikan Dayang Affizzah, Podivinsky Jan M.,